(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the linguocultural characteristics of numerative and measurative phraseological units in English and Uzbek languages. The study examines how numerical and measurement components function beyond their literal quantitative meanings and acquire symbolic, evaluative, and culturally specific interpretations. Using comparative, semantic, and linguocultural analysis, the research identifies similarities and differences in the usage of number - and measurement - based phraseologisms in both languages. The findings demonstrate that such units reflect national worldview, traditional beliefs, and collective experience. The results may be applied in translation studies, intercultural communication, and foreign language teaching.